2021
DOI: 10.1002/jsde.12553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the oat, horse chestnut, cowherb, soy, quinoa and soapwort extracts on skin‐mimicking monolayers and cell lines

Abstract: The main goal of the study was to compare the effect of aqueous extracts of oat (Avena sativa L.), horse chestnut (Aesculus hippocastanum L.), quinoa (Chenopodium quinoa Willd.), soapwort (Saponaria officinalis L.), cowherb (Vaccaria hispanica [P. Mill.] Rauschert) and soy (Glycine max L.) on model lipid monolayers mimicking the lipid membrane of keratinocytes and intercellular lipids of stratum corneum, and on human skin-related cell lines. Two lipid monolayers, consisting of a dipalmitoylphosphatidylcholine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(47 reference statements)
0
2
0
Order By: Relevance
“… 31 Jurek et al (2021) indicated that preservatives consisting of sodium benzoate and potassium sorbate at a 1:1 ratio induced cytotoxicity on HaCaT cells. 32 This suggests that the significant reduction in wound closure displayed by BFS and BFSAuNPs could be due to the preservatives used during the preparation of the extract.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Jurek et al (2021) indicated that preservatives consisting of sodium benzoate and potassium sorbate at a 1:1 ratio induced cytotoxicity on HaCaT cells. 32 This suggests that the significant reduction in wound closure displayed by BFS and BFSAuNPs could be due to the preservatives used during the preparation of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous reports we have compared synthetic and natural surfactants extracted from plants in terms of their effect on cell cultures of keratinocytes [24,25]. We have also attempted to correlate the keratinocytes' cytotoxicity with two assays used to quantify the protein (zein test) and lipid (oil emulsification test) solubilization potential [25].…”
Section: Introductionmentioning
confidence: 99%